Technical And Economic Analysis Of Catching Equipment Totaluo In Nike Fishing (Awaous Melanocephalus) In Gorontalo City - Tineke Wolok; Zhulmaydin Chairil Fachrussyah; Irwan Yantu (Universitas Negeri Gorontalo, 2019)
This study aims to describe totaluo and describe the feasibility status of nike (Awaous melanocephalus) fishing businesses using totaluo. This research was conducted in Gorontalo City in December 2018-February 2019. The analysis used in this study was descriptive analysis, cost analysis and R / C Ratio analysis. The results showed that Totaluo is shaped like two triangles which are joined together at one end and are equipped with nails. If observed, totaluo is similar to other types of fishing gear included in the Scoop net category. R / C Ratio analysis got a value of 2.68 so that the nike fishing business (Awaous melanocephalus) using totaluo could be declared feasible to be carried out / continued because the R / C Ratio value 0